The Effect of Work Experience, Work Communication, and Self Efficacy on Employee Performance at The Royal Pita Maha Resort Ubud, Gianyar - Dewa Ayu Nyoman Oka Sulastri; Ni Wayan Eka Mitariani; I Gede Yudhi Hendrawan (TALENTA Publisher, Universitas Sumatera Utara, 2025)
Hotel is one of the most popular accommodation services for tourists. In companies that provide accommodation services, of course, they must pay attention to the quality of their human resources because it will affect performance within the company. There is a phenomenon of decreased realization of company revenue along with customer complaints submitted on google reviews. Therefore, this study was conducted to examine the effect of work experience, work communication, and self efficacy on employee performance at The Royal Pita Maha Resort Ubud. The population in this study were employees at The Royal Pita Maha Resort Ubud, which numbered 85 employees. The sampling technique used is saturated sampling technique with data analysis technique, namely multiple linear regression analysis technique. The results showed that work experience, work communication, and self efficacy had a positive and significant effect on employee performance. Resort management is expected to improve aspects of increasing work experience, work communication, and self efficacy.